2003
DOI: 10.1074/jbc.m300617200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structural Studies on Human Erythrocyte α-Spectrin Tetramerization Site

Abstract: We have determined the solution NMR structure of a recombinant peptide that consists of the first 156 residues of erythroid ␣-spectrin. The first 20 residues preceding the first helix (helix C) are in a disordered conformation. The subsequent three helices (helices A 1 , B 1 , and C 1 ) form a triple helical bundle structural domain that is similar, but not identical, to previously published structures for spectrin from Drosophila and chicken brain. Paramagnetic spin label-induced NMR resonance broadening show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
91
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(99 citation statements)
references
References 46 publications
8
91
0
Order By: Relevance
“…[32][33][34]41,49 Spin label EPR studies provide the first experimental information on a local region of Helix B 0 in free bI-spectrin (not associated with aI-spectrin), with residues before 2071P in helical conformation (Helix B 0 ), and residues after 2071P in an unstructured conformation. 33,34 The predicted structure of free Helix B 0 of bI in this study also showed that 42 and bound 15,30,36 forms of a-spectrin have been observed experimentally, with the N-terminal junction region in aI-spectrin (residues 46-52) undergoing conformational changes, from unstructured to helical conformation, upon binding to the C-terminal fragment of b1-spectrin. 30,32 The conformation of the bI-Helix B 0 bound to G5 was predicted to consist of residues 2044-2068, a conformation different from the free form and a form in the presence of aI [ Fig.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…[32][33][34]41,49 Spin label EPR studies provide the first experimental information on a local region of Helix B 0 in free bI-spectrin (not associated with aI-spectrin), with residues before 2071P in helical conformation (Helix B 0 ), and residues after 2071P in an unstructured conformation. 33,34 The predicted structure of free Helix B 0 of bI in this study also showed that 42 and bound 15,30,36 forms of a-spectrin have been observed experimentally, with the N-terminal junction region in aI-spectrin (residues 46-52) undergoing conformational changes, from unstructured to helical conformation, upon binding to the C-terminal fragment of b1-spectrin. 30,32 The conformation of the bI-Helix B 0 bound to G5 was predicted to consist of residues 2044-2068, a conformation different from the free form and a form in the presence of aI [ Fig.…”
Section: Discussionsupporting
confidence: 70%
“…15,16 Thus, the affinity differences in tetramer formation between spectrin I and II are mostly attributable to the conformational differences between aI and aII. 17,18,42 The bI and bII C-terminal partial domains (residues 2008-2083 in bI and 2016-2091 in bII) are considered to be similar both in function and in conformation. These two regions exhibit high sequence homology ($70% identity and 80% similarity).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sequences of all plasmids were confirmed by DNA sequencing (DNA Services Facility, Research Resources Center, University of Illinois at Chicago). Recombinant proteins were expressed and purified as before [6,9]. The protein molecular masses were determined with high resolution LTQ-FT mass spectrometry (Proteomics and Informatics Services Facility, Research Resources Center, University of Illinois at Chicago).…”
Section: Methodsmentioning
confidence: 99%
“…Several hereditary hemolytic anemia diseases, such as hereditary elliptocytosis and hereditary pyropoikilocytosis, are found to be related to mutations in this region to give lower levels of spectrin tetramers in erythrocytes [7,8]. High resolution solution NMR studies of αI-N1 show that the region commonly referred to as the N-terminal partial domain of SpαI consists of an unstructured region (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and Helix C' (residue 21-45) [9]. The first triple helical bundle structural domain consists of residues 52-156.…”
Section: Introductionmentioning
confidence: 99%